PERANAN BAHAN ALAM DALAM PANDEMI COVID-19 - Yunita, Fenny (Fakultas Kedokteran Universitas Tarumanagara, 2021)
life. Various countries have used natural materials in dealing with the COVID-19 pandemic, such as China and Thailand. Indonesia has great potential in the development of natural ingredients considering that the nation's cultural heritage has been passed down from generation to generation in the form of herbal medicine which has also been equipped with various in vitro and in vivo studies as well as molecular docking, proving opportunities for developing natural materials as one of the modalities that can be utilized to overcome the COVID-19 pandemic. Some of them are turmeric/ginger, ginger, guava, meniran, sambiloto which have also been recommended in the guidelines for the use of herbs in dealing with COVID-19 in Indonesia.